Participation of Escherichia coli heat shock proteins DnaJ, DnaK, and GrpE in P1 plasmid replication. - Tilly, K (1989)
Low-copy-number plasmids, such as P1 prophage and the fertility factor F, require a plasmid-encoded replication protein and several host products for replication. Stable maintenance also depends on active partitioning of plasmids into daughter cells. Mini-P1 par+ and par plasmids were found to be destabilized by mutations in the dnaJ, dnaK, and grpE genes of Escherichia coli. The transformation efficiency and stability of mini-F plasmids were also reduced in the mutant strains. These results indicate that heat shock proteins DnaJ, DnaK, and GrpE play roles in the replication of plasmid P1 and probably also in of F.